2021
DOI: 10.1186/s12985-021-01630-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of oncolytic viruses in advanced or metastatic cancer: a network meta-analysis

Abstract: Background Oncolytic viruses (OVs) have shown prospects in advanced and metastatic cancer, and many clinical trials have been carried out. To compare OV therapies comprehensively and provide a categorized profile and ranking of efficacy and safety, a network meta-analysis was conducted. Methods A total of 5948 studies were screened and 13 randomized controlled trials with 1939 patients, of whom 1106 patients received OV therapies, comparing four OV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In addition, we performed a subgroup analysis according to hematological and non-hematological toxicity. Previous meta-analyses ( Li Y et al, 2020 ; Li Z et al, 2020 ; Zou et al, 2020 ; Xie et al, 2021 ) have only investigated a series of pairwise comparisons, so they failed to make comparisons without eligible clinical trials. In this study, we included not only RCTs but also selected single-arm trials and therefore gathered together comprehensive data.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we performed a subgroup analysis according to hematological and non-hematological toxicity. Previous meta-analyses ( Li Y et al, 2020 ; Li Z et al, 2020 ; Zou et al, 2020 ; Xie et al, 2021 ) have only investigated a series of pairwise comparisons, so they failed to make comparisons without eligible clinical trials. In this study, we included not only RCTs but also selected single-arm trials and therefore gathered together comprehensive data.…”
Section: Discussionmentioning
confidence: 99%
“…In the past five years, from phase I clinical trials, clinical data have been published with knowledge limiting safety. The general perception is that the OVs are generally safe; in all of those safety studies, adverse effects were limited to grade ≤3 and were observed for OVs with higher objective response rates (ORRs) [173,174]. As of 2 June 2023, 106 studies had undertaken OV in various trial phases, of which 33 studies were completed, according to ClinicalTrials.gov.…”
Section: Recent Clinical Trials For Ovtsmentioning
confidence: 99%
“…The results were negative, and patients receiving pelareorep, docetaxel and prednisone vs patients receiving docetaxel and prednisone had no effect on survival. A recent meta-analysis in advanced or metastatic cancer patients indicated that other oncolytic virotherapies may be more effective than pelareorep ( 69 ).…”
Section: Immuno-oncology Drug Development For Bone Metastasismentioning
confidence: 99%